PENGARUH MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN PASSING PADA PEMBELAJARAN SEPAK BOLAKELAS X IPA 2 DAN X IPA 3 DI SMAN 3 TAMBUN SELATAN - Rizky Gymnastiar Fadli; Sutirna, Dikdik Fauzi Dermawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of audiovisual media on passing skills in football learning among students of class X IPA 2 and X IPA 3 at SMAN 3 Tambun Selatan. The research was motivated by findings that many students struggle to master basic passing techniques, such as lack of accuracy, improper kicking force, and poor coordination. These issues are believed to be caused by the conventional teaching methods still widely used in physical education classes. The research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of two classes, each receiving different treatments: one with conventional learning and the other with audiovisual media-based learning. Data were collected through passing skill tests conducted before and after the treatment. The results showed a significant improvement in the passing skills of students taught using audiovisual media compared to those taught conventionally. Statistical analysis using a t-test revealed a significant difference between the experimental and control groups. Thus, it can be concluded that the use of audiovisual media in football learning significantly enhances students' passing skills. This study recommends the use of audiovisual media as an innovative alternative in physical education instruction, particularly to improve students’ basic motor skills such as football passing.